2003
DOI: 10.2298/gensr0303149p
|View full text |Cite
|
Sign up to set email alerts
|

Variability and heritability of average yield of onion bulb - Alium сeрa L.

Abstract: In order to investigate the variability of bulb yield, the trial was set up on an experimental plot of the Centre for Vegetable Crops in Smederevska Palanka during 1997 and 1998. The trial was performed by applying the method of random block system in five replications. Ten varieties of different geographical origins were included as the research material. The recorded values of the investigated features were determined by applying the variance analysis of a two-factorial trial model 2 (Hadživuković, 1991). Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 1 publication
6
5
0
Order By: Relevance
“…The coefficient of variance in the experiments was higher Broad-sense heritabilities for bulb yield were quite high, ranging from 0.62 to 0.85 for both populations, except for25CA10 in Juazeiro (Tables 3 and 5). The present results are in agreement with those found by Pavlović et al (2003), who reported broad-sense heritabilities of 0.73 and 0.77 in yield bulb in Serbia and Montenegro. Gashua et al (2013) have also reported high broad-sense heritability (0.71) in a Nigerian onion landrace.…”
Section: Resultssupporting
confidence: 94%
“…The coefficient of variance in the experiments was higher Broad-sense heritabilities for bulb yield were quite high, ranging from 0.62 to 0.85 for both populations, except for25CA10 in Juazeiro (Tables 3 and 5). The present results are in agreement with those found by Pavlović et al (2003), who reported broad-sense heritabilities of 0.73 and 0.77 in yield bulb in Serbia and Montenegro. Gashua et al (2013) have also reported high broad-sense heritability (0.71) in a Nigerian onion landrace.…”
Section: Resultssupporting
confidence: 94%
“…In F2 generation, heritability in narrow sense was 0.41 and 0.93 in broader (Table 5). Similar results in its researches were found by PAVLOVIĆ, (1999); PAVLOVIĆ et al, (2003); HAYDAR et al, (2007). Similar values for heritability of bulb height in its research were confirmed by RAJALINGAM and HARIPRIYA, (1998); MOHANTY et al, (2001a); SINGH et al, (2010); PAVLOVIĆ et al, (2003); PAVLOVIĆ et al, (2015).…”
Section: Graph 3 Ammi 1 Biplot For Total Yield Of 10 Onion Genotypessupporting
confidence: 88%
“…Following the results of MOHANTY, (2001a); MOHANTY, (2001b); MOHANTY and PRUSTI, (2002); PAVLOVIĆ et al, (2003), which proved similar results of genetic variance component on divergent genotypes and different traits of onion bulb, the results of this study are in coordination with most.…”
Section: Graph 3 Ammi 1 Biplot For Total Yield Of 10 Onion Genotypessupporting
confidence: 81%
See 2 more Smart Citations